Translation and validation of Brunel Mood Scale for Serbian athlete population - Rajkovic, Ivica (2014)
Ivica Rajkovic, 2014. Translation and validation of Brunel Mood Scale for Serbian athlete population. Master Thesis in Sport and Exercise Psychology. Department of Sport Sciences, University of Jyväskylä. 40p.